Biomechanical, histological, and computed X‐ray tomographic analyses of hydroxyapatite coated PEEK implants in an extended healing model in rabbit. Issue 5 (19th February 2018) - Johansson, Pär; Barkarmo, Sargon; Hawthan, Mohammed; Peruzzi, Niccolò; Kjellin, Per; Wennerberg, Ann
Abstract: A nanosized hydroxyapatite (HA) modification on polyetheretherketone (PEEK) using a novel spin coating technique was investigated in a rabbit model. Spin coating technique creates a 20–40 nm thick layer of nanosized HA particles with similar shape, size, and crystallinity as human bone. Some implants were designed with a perforating hole in the apical region to mimic a fusion chamber of a spinal implant. The coating nano‐structures were assessed using a scanning electron microscope. The in vivo response to HA‐PEEK was compared to untreated PEEK with respect to removal torque, histomorphometry, and computed microtomography. The HA‐coated and pure PEEK implants were inserted in the tibia and femur bone according to simple randomization. The rabbits were sacrificed 20 weeks after implantation. Removal torque analysis showed significantly higher values for HA‐PEEK. Qualitative histological evaluation revealed an intimate contact between PEEK and the bone at the threads and perforated hole. Histomorphometric assessment showed higher bone‐implant and bone area values for HA‐PEEK but without statistical significance. The effect of the HA coating showed most prominent effect in the removal torque which may be correlated to an alteration in the bone quality around the HA‐PEEK implants. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1440–1447, 2018.